Cement Pulmonary Embolus Complicating Percutaneous Vertebroplasty - Khan, Mo (Radiol Case Rep, 2016)
We present the case of a 63-year-old woman who suffered a cement pulmonary embolus that resulted from methylmethacrylate extravasation into the paravertebral venous plexus during percutaneous vertebroplasty. We discuss the radiographic diagnosis and strategies for prevention and treatment.